Dampak Sosial Media Marketing Melalui Instagram terhadap Minat Beli Konsumen Coklat Majapahit Mojokerto - Alifiah Putty Agustia; Sri Tjondro Winarno; Sigit Dwi Nugroho (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the effect of context through Instagram social media on the buying interest of Majapahit Chocolate Consumers in Mojokerto, to determine the effect of communication through Instagram social media on the buying interest of Majapahit chocolate consumers in Mojokerto, to determine the effect of collaboration through Instagram social media on the buying interest of Majapahit chocolate consumers in Mojokerto. , to find out the effect of collaboration through Instagram social media on Mojokerto Majapahit Chocolate Consumer Buying Interest and to determine the effect of connections through Instagram social media on Majapahit Mojokerto Chocolate Consumer Buying Interest. The research hypothesis was tested using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). PLS is a component or variant-based structural equation model (SEM). Hypothesis testing is done by testing Variance-based SEM or Partial Least Square (SEM-PLS) with the warppls program. SEM-PLS is used for exploratory research. In other words, the PLS approach is more suitable for prediction purposes. Context variables have a real and positive and significant effect on consumer buying interest in Mojokerto Majapahit Chocolate. Communication variable has no significant effect on consumers' buying interest in Chocolate Majapahit Mojokerto. Collaboration variable has a significant and positive effect on consumers' buying interest in Chocolate Majapahit Mojokerto. The Connection variable has a significant and positive effect on consumer buying interest in Mojokerto Majapahit Chocolate.